Antioxidant Activity, Physicochemical Properties of Pasteurized Milk by Red Ginger (Zingiber officanale var Rubrum) and Pandan Leaves (Pandanus amaryllifolius) Addition - Kusuma, Muh. Wahyu; Malaka, Ratmawati; Maruddin, Fatma (Journal of Ecohumanism, 2025)
Pasteurized milk aims to make functional pasteurized milk products by adding red ginger and pandan leaves. This study aims to evaluate the use of red ginger and pandan leaves in terms of antioxidant activity and physicochemical changes (organoleptic and color tests L *, a *) in pasteurized milk products. The study design used a completely randomized factorial design consisting of 3 treatments, namely the level of red ginger addition (%) (1.5, 4.5, 7.5), the level of pandan leaves addition (%) (15, 25, 35), and four replications. Finely ground ginger and pandan leaves are added with water in a ratio of 1-4 and homogenized; then the red ginger and pandan leaf extracts are separated from the pulp by filtering. Furthermore, the red ginger and pandan leaf extracts are heated using an autoclave sterilizer at a temperature of 1050 C for 5 minutes. The parameters observed were antioxidant activity using the DPPH method, measuring viscosity using the NDJ-8s viscometer method, and L * and a * colors using the digital color meter test method (T 135). After cooling, the milk is ready to be consumed and poured into a plastic bottle container. The parameters observed were antioxidant activity, viscosity, L* and a* colors. The results showed that the addition of red ginger and pandan leaves significantly increased (P<0.01) antioxidant activity, and viscosity, but decreased the L* and a* colors. It was concluded that the addition of 7.5% ginger and 25% pandan leaves was the best treatment for pasteurized milk products.